2013
DOI: 10.1111/nuf.12041
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Potential Muslim Organ Donors' Perspectives on Solid Organ Donation: Lessons for Nurses in Clinical Practice

Abstract: Nurses need to know that organ donation is compatible with Islam and that religious leaders, family, sociocultural beliefs, legal requirements, informed decision making process, and Ramadan are important aspects that need to be considered in order to be able to provide culturally senstive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Generally, there are fewer issues around receiving transplants than around donation . There is no difference in opinion among South Asians of different faiths living in the UK regarding whether they would accept an organ transplant if needed .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, there are fewer issues around receiving transplants than around donation . There is no difference in opinion among South Asians of different faiths living in the UK regarding whether they would accept an organ transplant if needed .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found that lack of public knowledge and understanding of the Islamic rulings on organ donation and transplantation is the major culprit . In general, Muslims are more willing to donate during their lifetime and to their family ; most concerns related to organ donation have to do with deceased donations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…necessidade da existência de profissionais que se sintam preparados para atuarem nesta área, o que pode auxiliar no indice de transplantes realizados(MULIIRA;MULIIRA, 2014;MANYALICH et al, 2011, através de atividades educativas que venham conscientizar a população. E assim, sem dúvida, quando esses profissionais se sentirem seguros tanto técnico quanto emocionamente, poderão realizar suas atividades nessa área tanto nas unidades hospitalares quanto nos demais segmentos sociais e, portanto na população em geral.Além disso, vale destacar que na visão dos alunos do quarto ano, tornase imprescindível que os profissionais compreendam a importância da doação e se envolvam neste processo.…”
unclassified